Stress and anxiety in handball college athletes - Venditti Júnior, Rubens (2019)
Background: Competition is intrinsic to sport and can generate so many emotional states with the potential to influence performance. Among these states, anxiety appears as emotional element and, in addiction with stress process, they configure themselves as psychological aspects to be observed. These aspects are not different in college sports scope and appear intensively at competition´s periods. Objective: To identify the level of trait anxiety, state anxiety and stress process in university handball athletes of two different teams at São Paulo State in Brazil. Methods: The sample of this study was composed of 22 male handball university athletes, with a mean age of 21±1.8 years. The athletes answered to the “State-Trait Anxiety Inventory” (STAI) and to “Situations of Stress in Handball” (SSH). Results: The results indicated that the situations most cited by athletes as causing stress were: “miss 7-meter shots at decisive moments of the game”; “Being lost to technically inferior staff”; “Miss a pitch completely free”; “Arbitration hamper my team”; “To be excluded in the decisive moments of the game” and “to concede a goal due to defensive failure”. Concerning anxiety, the results showed that all athletes showed, in general, levels of anxiety-trait and anxiety-state considered moderate (36.59 and 41.45, respectively). Conclusion: In view of the results, it can be seen that the athletes investigated presented some situations of play as stressors and that, in relation to anxiety, the levels of the athletes are moderate.